When Dialysis “Becomes Life”: Pediatric Caregivers' Lived Experiences Obtained From Patient-Reported Outcomes Measures - Levy Erez, Daniella; Meyers, Melissa R.; Raman, Swathi; Thomas, Melissa; Furth, Susan; Forrest, Christopher B.; Denburg, Michelle (Frontiers in Pediatrics, 2022)
Introduction: Qualitative research reveals significant caregiver impact resulting from managing children requiring chronic dialysis but offers few quantitative measures of their lived experiences. Materials and Methods: This cross-sectional study included 25 caregivers of children on chronic peritoneal dialysis (PD) and hemodialysis (HD) enrolled from 2018-2019 at a large pediatric dialysis program in the U.S. Patient Reported Outcomes Measures Information System (PROMIS) measures and free text commentary were collected and analyzed to evaluate the self-reported impact and well-being of these caregivers. Results: Among all dialysis modalities, caregivers’ positive affect (43.4  10) and general life satisfaction (45.1  11.5) were significantly lower than the general adult population. Compared with HD caregivers, PD caregivers demonstrated significantly more fatigue and sleep disturbance and less positive affect and life satisfaction. Amongst HD caregivers, sleep disturbance, positive affect, and meaning/purpose differed significantly from the general population. Analyses of text commentary revealed that caregivers also expressed the feelings of loss, importance of knowing the impact of dialysis prior to initiation, need for a support group, and value of home nursing. Conclusions: Caregivers of children on chronic dialysis had significantly poorer self-rated health and well-being compared with the general adult population. This may be due in part to their feelings of social isolation. Our findings highlight opportunities to improve caregivers’ lived experiences.